Pengaruh financial distress, opinion shopping, prior opinion, dan audit tenure terhadap opini audit going concern - Elisabeth Sry Rahayu Sitindaon; Hendi Subandi (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2025)
Purpose – This research aims to investigate the effect of financial distress, opinion shopping, prior opinion, and audit tenure on a going-concern audit opinion. The data used in this research is secondary data sourced from audited published financial reports and annual reports of property and real estate companies between 2017 and 2022. Methods – The population includes property and real estate companies listed on the Indonesian Stock Exchange, from which 132 samples are selected through a non-probability sampling technique with a purposive sampling. This research uses logistic linear regression analysis as a data analysis technique. Findings – The findings of this research indicate that all the independent factors, including financial distress, have been shown to have a beneficial impact on the acceptance of a going-concern audit opinion. Empirical evidence has shown that engaging in opinion shopping has a beneficial impact of acceptance of a going-concern audit opinion. Prior opinion has been shown to have a beneficial impact on the acceptance of a going-concern audit opinion. Research has shown that the length of audit tenure positively influences the likelihood of receiving a going-concern audit opinion. Implications - Contribution to literature regarding the factors that need to be considered in evaluating sustainability, particularly for property and real estate businesses. Originality - Focuses on property and real estate businesses, which have not previously been the focus of research in identifying factors that influence the acceptance of going concern audit opinions.